Revolutionizing Farming: Innovative Feeds and Techniques at Di Bambo Farm and Cattle and Goat Group in Jambula, Ternate Island - Sariffudin Fatmona; Sri Utami; Gunawan Gunawan (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Partner Farmers are increasingly experiencing a reduction in livestock feed resources in their environment over time. This is due to the conversion of lands, where these feed resources used to grow, into residential areas. Such conditions have made it somewhat challenging for the farmers to find adequate livestock feed. Additionally, the farming practices have not fully embraced technology for management. These conditions have led to a qualitative decline in the productivity of cattle, particularly in terms of body weight, even though the population has increased quantitatively. The objectives of this Community Partnership Program (PKM) are as follows: To establish a robust institution and ensure that the cattle are legally registered with the relevant department; To enhance farmers' understanding of cattle reproduction, including the ability to recognize estrus, productive age, and post-mating care; and to provide knowledge and skills to the partners regarding the production of Urea Molasses Blocks. The approach involves three methods: Lectures and discussions, Demonstration plots, and activity evaluation. The results of this PKM show that the partners' knowledge has improved, especially in the areas of livestock reproduction and the development of new Urea Molasses Blocks (UMB) feed.